Health and wellness centers: a paradigm shift in health care system of India? - Solanki, Hariom K.; Rath, Rama Shankar; Silan, Vijay; Singh, Satya V. (International Journal Of Community Medicine And Public Health, 2020)
An ambitious attempt to achieve the goal of universal ‘comprehensive’ primary care through health and wellness centres under the Ayushmann Bharat Scheme (ABS) has been made by the Ministry of Health and Family Welfare, Government of India. The scheme has widened the package of services available to beneficiaries and it also envisages continuum of care. However, there are pre-existing weaknesses in the three tired public health system in India which may threaten the success of this scheme. In this article we describe and analyze the newer services or initiatives at the health and wellness centres under the ABS. We also attempt to identify the Strengths, weaknesses, threats and opportunities associated with this initiative.